2007
DOI: 10.1016/j.margeo.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of mud flows, chemoautotrophic communities, and biogeochemical habitats at Håkon Mosby Mud Volcano

Abstract: Marine mud volcanoes are significant source locations contributing to the marine methane cycle. Enhanced heat flow, unique chemoautotrophic communities, occurrence of massive gas hydrates and large gas plumes are direct evidences of elevated methane concentrations and the dynamic environment of mud volcanoes. Related to the high concentrations and large inventories of CH 4 in surface sediments only a fraction of the methane is exported to the bottom water. This is mainly due to chemoautotrophic communities oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 35 publications
1
82
0
Order By: Relevance
“…The spatial gradient in fluid flow rates across the HMMV has been found to create different niches for benthic assemblages, characterized by specific transport regimes and biogeochemical settings Jerosch et al 2007;Feseker et al 2008). Some temporal variability of mud volcanism was indicated by changes in absolute seafloor temperature between the different years (Feseker et al 2008), and variations in the microbathymetry of mud flows in the central and southern HMMV (Foucher et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial gradient in fluid flow rates across the HMMV has been found to create different niches for benthic assemblages, characterized by specific transport regimes and biogeochemical settings Jerosch et al 2007;Feseker et al 2008). Some temporal variability of mud volcanism was indicated by changes in absolute seafloor temperature between the different years (Feseker et al 2008), and variations in the microbathymetry of mud flows in the central and southern HMMV (Foucher et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Videographic observations during ROV sampling indicated minor changes in overall habitat distribution within this time period. Hence, we have based the areal calculations on the detailed habitat map obtained in 2003 (Jerosch et al 2007). The gray mat habitat (III) was only recently described Lichtschlag et al 2010) and not considered as separate habitat in the previous habitat analyses (Jerosch et al 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Perez-Garcia et al (2009) described the evolution of the HMMV over the last 330,000 years and, based on acoustic and seismic data, inferred the presence of a pseudo-mud chamber and a funnel-shaped geometry of the shallow part of the conduit. Field observations made during successive oceanographic expeditions have emphasized the concentric zones of litho-types, as well as of geochemical and biological processes at the surface of the mud volcano (Milkov et al 1999de Beer et al 2006;Jerosch et al 2007), and demonstrated an exceptionally high activity of fluid and gas ejections through the seabed Feseker et al 2008). Geothermal modelling indicates aqueous flow rates reaching 4-10 m year −1 at the centre of the mud volcano, rapidly decreasing to less than 1 m year −1 in its outer part (Feseker et al 2008).…”
Section: Geological Settingmentioning
confidence: 99%
“…Colonization devices were deployed by ROV Victor 6000 (Ifremer,154 France) and recovered by the ROV Quest 4000 (MARUM, Germany) after 12 months (Table 1) 155 in the south Hummocky periphery of the mud volcano where there was generally a high density 156 of siboglinids (>50%) and lower density of Beggiatoa spp. (<20%) (Jerosh et al, 2007). 157 158…”
Section: Introduction 43mentioning
confidence: 99%